Effectiveness of digital behaviour change interventions for promoting physical activity in adolescents with overweight and obesity: a systematic review and meta-analysis - Jahn Kassim, Puteri Shanaz; Muhammad, Noor Azimah; Abdul Rahman, Nur Faraheen; Mohd Sidik, Sherina; A. Essau, Cecilia; Shah, Shamsul Azhar (SAGE Publications, 2025)
Background: Obesity in adolescence is associated with many adverse health and well-being outcomes. Physical activity plays an important role in the prevention of obesity; however, many adolescents with overweight and obesity are physically inactive. Digital behaviour change interventions (DBCI) are increasingly used to increase physical activity; however, there is insufficient evidence on their use in promoting physical activity among adolescents with overweight and obesity, including its active components. This review aims to evaluate the effectiveness of DBCIs in promoting physical activity among adolescents with overweight and obesity and to identify the behaviour change techniques (BCTs) used in these interventions. Methods: Seven electronic databases were searched for randomized controlled trials and quasi-experimental studies evaluating DBCIs for physical activity promotion in adolescents with overweight and obesity aged 10–19 years. The risk of bias in the included studies was assessed using Cochrane's Risk of Bias tool 2 and ROBINS-I tool. Meta-analyses were performed using random effects models. The BCTs used within the DBCIs were coded using the Behaviour Change Technique taxonomy (v1). Results: Eighteen studies involving 1769 participants were included. DBCIs showed a large, significant positive effect on total physical activity (SMD = 1.61, 95% CI: [0.56, 2.66], p = 0.003), but non-significant effects on moderate-to-vigorous physical activity (MVPA) (SMD = 0.16, 95% CI: [−0.39, 0.71], p = 0.56) and step count (SMD = −0.10, 95% CI: [−0.52, 0.32], p = 0.65). High heterogeneity was observed in total physical activity and MVPA analyses. The most frequently used BCTs were information about health consequences, goal setting, self-monitoring, feedback on behaviour and social support. Conclusion: DBCIs can effectively promote overall physical activity among adolescents with overweight and obesity, although their impact on MVPA and step count remains unclear. Future research should focus on optimizing BCT combinations and improving long-term engagement while addressing intervention effect variability. Systematic review registration: PROSPERO CRD42021270008